Akademik Smail Balić Bošnjak, humanist, orijentalist evropljanin / Academician Smail Balić Bosniak, Humanist, Orientalist, European - Hadžić, Salim A. (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
In March 2022, twenty years have passed since the death of academician Smail Balić. He was an erudite, an exceptionally skilled Orientalist, a translator, a versatile researcher of cultural and intellectual history, an advocate of dialogue between religions and, most importantly, a humanist. With his work on sources and materials, he left an indelible and deep mark in the study and interpretation of historical and cultural facts from the past of Bosnia and Herzegovina, as well as the wider region. He focused, devotedly and vigilantly watched over the cultural and scientific heritage of Bosniaks, which he studied all his life through his professional and humanitarian work in Austria.